COMPARISON OF STORE AND FORWARD METHOD OF TELEDERMATOLOGY WITH FACE-TO-FACE CONSULTATION - Rashid, Eanas; Ishtiaq, Osama; Gilani, Salman; Zafar, Asif (Journal of Ayub Medical College Abbottabad, 2003)
Background: To compare the accuracy of store and forward method of teledermatology with the traditional face-to-face consultation. Methods: The comparison was done between Institute of Dermatology King Edward Medical College Lahore that served as teledermatology center and Dermatology Department of Pakistan Institute of Medical Sciences Islamabad from where patients were selected. TelmedpakÃ’ provided the technical support. Thirty three patients were selected from outpatient department of PIMS and images were taken using a digital camera. Images were stored in computer and were sent to Institute of Dermatology via email for Teleconsultation along with a short history and examination findings. Diagnosis of consultant after face-to-face consultation was then compared with the image based diagnosis that is after teleconsultation. Results: In 81% of the cases the diagnosis on face-to-face consultation was same (p<0.05) while in 18% of the cases the two diagnoses differed. In 9% (n=3) of the cases, image resolution was not good but out of these three, diagnosis was same in two and differed in one case. Conclusion: This study concludes that store and forward method of teledermatology is reliable and can provide a means of increasing access to dermatological care in rural and under-served areas. Keywords: Teledermatology, Teleconsultation, Telemedicine